2013
DOI: 10.1007/s10815-013-0091-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of semen quality, occupational exposure to environmental factors and lifestyle on recurrent pregnancy loss

Abstract: Purpose This study aimed to investigate the effect of male semen quality, occupational exposure, and lifestyle on recurrent pregnancy loss (RPL). Methods Information on couples' occupational exposure and lifestyle was collected using a detailed questionnaire from 68 RPL couples and 63 randomly selected healthy controls. Semen parameters were estimated by computer-assisted sperm analysis, and sperm nuclear status was detected with aniline blue (AB) staining. Results Patients in the RPL group had significantly l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…Comparing the distribution of AB aniline blue stained sperm (Table 1, Figure 1C) of RPL patients with that of the control group, it was found that the percentage of intermediate stained spermatozoa had significantly increased along with a significant decrease in the percentage of normal protamine packaged spermatozoa (light stain). About three studies have been undertaken to measure aberrant sperm chromatin packaging by AB staining in RPL patients [Kazerooni et al 2009;Ruixue et al 2013;Zidi-Jrah et al 2016]. Our results are congruent with those obtained by these three works, which verified a lower rate of spermatozoa with normal nuclear chromatin condensation from men with spontaneous recurrent abortion compared with the control group.…”
Section: Resultssupporting
confidence: 89%
“…Comparing the distribution of AB aniline blue stained sperm (Table 1, Figure 1C) of RPL patients with that of the control group, it was found that the percentage of intermediate stained spermatozoa had significantly increased along with a significant decrease in the percentage of normal protamine packaged spermatozoa (light stain). About three studies have been undertaken to measure aberrant sperm chromatin packaging by AB staining in RPL patients [Kazerooni et al 2009;Ruixue et al 2013;Zidi-Jrah et al 2016]. Our results are congruent with those obtained by these three works, which verified a lower rate of spermatozoa with normal nuclear chromatin condensation from men with spontaneous recurrent abortion compared with the control group.…”
Section: Resultssupporting
confidence: 89%
“…Semen parameters, such as sperm concentration, motility, viability, and morphology provide useful insight into the semen quality. However, the role and the correct interpretation of these semen parameters remain unclear and their implications on recurrent pregnancy loss are debatable ( Ruixue et al ., 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are many factors which effect semen parameters such as environmental issues, tight under garments which raises the local temperature, life-styles, occupational hazards and sleep deprivation adversely effect semen parameters. [ 1 2 3 4 ] Added to these smoking, which causes harmful effects to probably every tissue of the human body[ 5 ] effects semen parameters as well. There is conflicting findings on the effect of smoking on the quality of semen.…”
Section: Introductionmentioning
confidence: 99%